HUMAN’S CONSCIOUSNESS AS THE HIGHEST LEVEL OF BEING REFLECTION FIXATION IN THE UNIVERSAL FORMS OF COMMUNICATION: THE PHILOSOPHIC ASPECT - Харченко, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the philosophic analysis of the phenomenon of consciousness as the way of communication realization is carried out.